Allocation of costs in projects of multiple uses of water resources: an application of Shapley value - Lincoln Sarli Cesar Guedes Lima (2009)
This work aimed at to analyze the allocation of the financial costs in projects of multiple uses in the section of water resources, among different purposes of use of the water. Such projects are cheaper because, they present scale savings due to the shared use of the resources, thus, the central problem that appears is as allocating the costs among the participants of the project. It was taken as example the fishing reservoir in the municipal district of Capistrano, and the one of Figueiredo in the municipal district of High Saint, both in CearÃ. The methodology used to allocate the costs among the purposes of the projects was given by the rule of defined allocation as value of Shapley, belonging to the theory of the cooperative games. For the project of the Fishing reservoir, the allocated values of the total cost among the integral purposes, they satisfy the beginnings of justness, resulting in a fair and efficient solution, what indicates for that case studied that the solution is in the nucleus of the game. A different conclusion is removed of the results generated for the other used example. The obtained allocations are not in agreement with one of the beginnings of justness, indicating a solution no belonging to the nucleus of the game, which defines impartiality in the allocations obtained for the project of Figueiredo's reservoir.